P162 Analysis of and lessons from the multiple screening episodes in uk's tuberculosis pre-entry screening programme: october 2005 to december 2016. (15th November 2017) - Muzyamba, MC; Harris, R; Zenner, D
Abstract : Background: The UK has been carrying out pre-entry tuberculosis (TB) screening for all long term migration visa applicants in 15 pilot countries since October 2005. Screening was subsequently rolled out to visa applicants in 101 high TB incidence (≥40/100 000 population) countries. Individuals screened free of pulmonary TB are issued with medical clearance certificates valid for 3 and 6 months for those with or without close contact with a TB case, respectively. Consequently, individuals who travelled to the UK on multiple occasions need rescreening once their certificates have expired. Screening identifies prevalent TB cases among migrants thereby reducing incidence and onward transmission in the UK. Methods: Our study used a cohort of migrants from 40 high incidence countries screened for TB pre-entry by the International Organisation for Migration between October 2005 and December 2016. All applicants screening prior to certificate expiry were excluded. Odds ratios (ORs) and relative risk ratios (RRRs) were estimated using logistic and multinomial logistic regression, respectively, to identify factors associated with multiple screening. Results: The cohort consisted of 8 55 591 migrants screened for pulmonary TB. 7 29 232 (85.0%) were screened once but 1 26 358 (15.0%) were screened ≥2 times. After adjusting for age and sex, the factors associated with being screened ≥2 times included being diagnosed with TB (OR 3.40; 95% CI 2.99–3.85), close contact with TB (OR 1.29 95% CI 1.18–1.40) and certain visa types (Settlement: 1.95; 95% CI 1.93–1.97, baseline Student visa). Applicants from the Indian sub-continent were more likely to screen multiple times than other regions. RRRs for individual categories using multinomial logistic regression were similar to overall ORs. Multiple screenings were also associated with increased TB detection. Conclusions: Being diagnosed with TB, being a close contact of a TB case and those applying for settlements visa were more likely to be screened multiple times. This information could be used for targeted follow up of individuals likely to screen multiple times and determine their risk of TB.